Internet banking services and their impact on customer's: Applied Research on Sample of Iraqi Commercial Banks (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research examines the issue of Internet banking services and their impact on customer's perceived value to know the potential of Iraqi commercial Banks to provide Internet banking services as well as determine the customer's level of perception of the value of such services. The research aims to demonstrate the effect that Internet banking services have on the customer's perceived value and to find how online banking services can be used to add value that the customer perceive. The main findings were that research sample banks don't have a sophisticated network of electronic Windows through which banking services are provided to allow customers to manage their accounts, and perform various operational operations through the bank's website, and there are certain constraints, such as weak or blocked Internet access, have frequent technical failures in electronic systems and the bank's communication networks, that prevent timely delivery of electronic banking services to customers, and to have discrepancies between private Banks (gulf bank of commerce) and government (Rafidain bank) for the hubs of Internet banking and the customer's perceived value from the viewpoint of the research sample.